Anangula before and after: to the 50th anniversary of Soviet-American archaeological expedition on the Aleutian Islands - Tabarev A.V. (Вестник археологии, антропологии и этнографии)
The purpose of this work is to analyze the events in scientific life that preceded and followed the first Soviet-American archaeological expedition to the Aleutian Islands 50 years ago (1974) and the excavations of the Anangula Site, the materials of which date back to ca. 9,000 years ago. The used sources include various publications by Russian and foreign authors, highlighting the key episodes of international dialogue and the stages of the formation of American studies in the Kunstkamera (St. Petersburg), the Institute of Ethnography (Moscow), and the Institute of History, Philology and Philosophy (Novosibirsk), as well as the information on the participation of Russian scientists, with reports, at major international forums, periodicals, and scientific chronicles, freely available archival data, and also records from family collections. The dynamics and forms of academic cooperation between Russian and North American archaeologists and ethnographers (exchanges of visits, conferences, exhibitions, joint projects, publications) are traced during different stages — in the 1900s–1930s, 1950s–1970s, 1980s, 1990s, and early 2000s. The initial period featured the interest of the American side in the study of materials from Siberia and Northeast Asia in the person of such specialists as A. Hrdlicka, F. Rainey, and W. Laughlin, and the late 1960s period — the institutional, structural, and thematic development of American studies in several scientific centers in Russia. The specifics of changes in the structure of financing, and the role of the grant system (Russian and foreign scientific foundations) since the 1990s are noted. As a result, a number of conclusions have been drawn about the regularity of the appearance and implementation of the project on the Aleutian Islands, the role of Siberian researchers (A.P. Okladnikov, A.P. Derevianko, R.S. Vasilievsky) in the development of such areas as American studies and Pacific archaeology in science and education, the long-term effect of the “Anangula legacy” for the next generations of Russian and North American archaeologists, as well as about the current state of the research in the area.